DIPLOMASI INDONESIA DALAM PENETAPAN BATAS PERAIRAN DENGAN TIMOR LESTE - Rizka Kurnia Dewi; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
After Timor Leste gained independence from Indonesia, there was a change in the status of the territory that was originally Indonesian and now belongs to Timor Leste. But nearly two decades of East Timor's independence, there are no stipulations and rules regarding the maritime territorial between Indonesia and Timor Leste which should be the focus of the government to avoid the threat of encroachment. This study uses qualitative methods and uses the perspective of Realism in which the Realist offers the concept of National Interests, the basic views or assumptions of this perspective include upholding national security values and the existence or survival of the state. After taking an intensive approach, including through a number of bilateral meetings, maritime boundary forums conducted by the Indonesian government, the reality that occurred on the ground is not in accordance with the intensive approach that has been taken by the Indonesian government. The reason for the unfinished land border makes an excuse not to immediately settle the sea borders that are in the borders of Indonesia and Timor Leste. Indonesia's attitude which prioritizes resolving land borders over sea borders provides opportunities for foreign countries and foreign citizens to commit violations. Therefore, the Indonesian government must be consistent in inviting Timor Leste in the determination of borders of water territories in order to produce clarity about exploitation rights and reduce border violations that prejudice border society. Keywords: Waters Boundary ,Diplomacy,  Maritime